Evaluation of pacemaker performance using computer simulation. - Dassen WR; Den Dulk K; Gorgels AP; Brugada P; Wellens HJ (Pacing & Clinical Electrophysiology, 1985)
A description is given of a mathematical model of impulse conduction through the heart. The model can be used to evaluate the best pacing mode for the individual patient and to develop new pacemakers. This allows study of the influence of different parameters related to the behavior of the heart or pacemaker. Two examples using a model of a DDD pacemaker and two examples describing simulation of an antitachycardia pacing system are given to illustrate how the performance of pacemakers under different conditions can be simulated.